Investigation of Genetic Susceptibility to Blastomycosis Reveals Interleukin-6 as a Potential Susceptibility Locus - Richard M. Merkhofer (American Society for Microbiology, 2019)
ABSTRACT Genetic differences are hypothesized to underlie ethnic disparities in incidence rates of the endemic systemic mycoses, including blastomycosis. Individuals of Hmong ancestry display elevated risk for this serious fungal infection. Here, we interrogated the genomes of Wisconsin (WI) Hmong blastomycosis patients using homozygosity mapping to uncover regions of the genome that are likely shared among the greater Hmong population and filtered for variants with high potential to affect disease susceptibility. This approach uncovered 113 candidate susceptibility variants, and among the most promising are those in genes involved in the interleukin-17 (IL-17) response. In particular, we identified 25 linked variants near the gene encoding IL-6 (IL6). We validated differences in cytokine production between Hmong and European volunteers and formally demonstrated a critical role for IL-6 in the development of adaptive immunity to Blastomyces dermatitidis. Our findings suggest that the dysregulation of IL-17 responses underlies a recently reported and poorly understood ethnic health disparity. IMPORTANCE Blastomycosis is a potentially life-threatening infection caused by the fungus Blastomyces dermatitidis. As with related fungal diseases, blastomycosis is noted to affect some populations more than others. These patterns of illness are often not related to predisposing conditions or exposure risks; thus, genetic differences are thought to underlie these health disparities. People of Hmong ancestry in Wisconsin are at elevated risk of blastomycosis compared to the general population. We studied the genetic codes of Hmong blastomycosis patients and identified candidate sites in their genomes that may explain their susceptibility to this infection. We further studied one particular region of the genome that is involved with the immune processes that fight B. dermatitidis. Our work revealed population differences in the response to fungi. A better understanding of the genetic underpinnings of susceptibility to infectious diseases has broader implications for community health, especially in the paradigm of personalized medicine.